Impact of the Covid-19 Pandemic on India's Digital Payment System: Exploring the growth and challenges of digital payments in India during the Covid-19 pandemic (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The benefits of digital payments over cash are many, including their greater ease, security, andtransparency. The banking sector's provision of digital payment instruments like debit cards, mobilebanking, mobile wallets, etc. is vital in this pandemic context. Possible acceleration of the trend toward acashless society as a result of the worldwide pandemic. People continue to place a lot of trust inpayment systems since they have shown to be dependable and long-lasting, which has led to the growthof online payment methods. However, typical transaction volumes dropped as a result of the lockout andbusiness closures. Helping the recovery and contributing to the creation of this new standard will needrapid progress and assistance from the digital payments ecosystem in the Post-COVID era. The increasein digital payments over the past three years and their significance during pandemics are the primarytopics of this study.